Concept of Analysis in The Context of Critical Thinking - Acarer, Ayşe (Espacio Abierto, 2025)
In this study, the effect of the concept of analysis in Michel Foucault understands of knowledge on his general way of thinking and the type of critical thinking he wanted to create will be investigated. Although analysis is directly related to the analytical way of thinking in terms of Aristotelian logic, it is characterized separately from this context in Foucault’s thought. While Foucault positions analysis at the center of change in the context of the archaeological method, analysis in the Aristotelian sense is analytically focused. These ways of thinking, which are different from each other and often contradict each other, attribute different qualities to a common concept. In this study, the points where the meaning attributed to analysis in Foucault differs from the analytical way of thinking in the context of its relationship with other basic concepts will be included